2009
DOI: 10.3324/haematol.13299
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of molecular subtypes in acute myeloid leukemia based on gene expression profiling

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nR.G.W. Verhaak et al. between both AML sample populations. Mutational analyses to detect recurrent mutations in AML were performed as previously described. [13][14][15][16] All supervised class prediction analyses were performed with Prediction Analysis for Microarrays (PAM) software version 1.28 in R version 2.1.0. 17 Clinical, cytogenetic and molecular information as well as the gene expression profiles of all primary AML cases is available at the Gene Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
389
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(404 citation statements)
references
References 22 publications
13
389
1
1
Order By: Relevance
“…The sensitivity to predict FLT3-ITD positivity was only around B70.0% (Supplementary Tables S14 and S15). However, this result is in agreement with recent data from Verhaak et al, 17 who reported a positive predictive value for FLT3-ITD aberrations of 77%. As many FLT3-ITD cases were intercalating with FLT3 wild-type cases (Supplementary Figure S7), one can speculate that a FLT3-ITD signature might become more robust on further evaluation of the ratio of the mutated allele in comparison to the wild-type allele.…”
Section: Cebpa-mutated Cases (Highlighted In Supplementarysupporting
confidence: 82%
“…The sensitivity to predict FLT3-ITD positivity was only around B70.0% (Supplementary Tables S14 and S15). However, this result is in agreement with recent data from Verhaak et al, 17 who reported a positive predictive value for FLT3-ITD aberrations of 77%. As many FLT3-ITD cases were intercalating with FLT3 wild-type cases (Supplementary Figure S7), one can speculate that a FLT3-ITD signature might become more robust on further evaluation of the ratio of the mutated allele in comparison to the wild-type allele.…”
Section: Cebpa-mutated Cases (Highlighted In Supplementarysupporting
confidence: 82%
“…Finally, we analyzed the expression status using available microarray expression data 37 of the target genes in patients (n ¼ 33) harboring an inv (16) translocation. This analysis confirmed that CBFb-MYH11 target genes are higher expressed than CBFb/ RUNX1 or RUNX1 only target genes (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
“…To gain insight into the potential clinical relevance of these 214 AE9a direct targets, we analyzed their expression levels in a published large-scale human AML profiling study 37,38 through Oncomine (Compendia Bioscience). Approximately 30% of these genes show t(8;21)-specific up or down-regulation in the same direction as in AE9a leukemia mice compared with AML with other karyotypes, including 19 of 60 AE9a targets that were enriched in both HA and AML1 ChIP-chip assays mentioned in the previous section (supplemental Table 3).…”
Section: Expression Levels Of Ae9a Direct Targets In Aml Patientsmentioning
confidence: 99%